Decentralizacja - instrument racjonalizacji finansów sektora publicznego - Markowska-Bzducha, Ewa (Decentralization - a Tool of the Public Sector Finance Rationalization, 2009)
The aim of this paper is to present the public sector sizes and the public finance decentralization level in countries of the European Union and to emphasize the possibility of its usage as a way to improve the rationality of the public finance management in times of crisis. The analysis was concentrated on two indicators showing the public finance condition in the examined countries in years 2001, 2005 and 2007 (public expenditures as % of GDP and municipal expenditures as % of total public expenditures). The analysis shows that the share of public sector expenditures in the GDP decreased in most EU countries while the level of public finance decentralization increased. These tendencies are definitely positive from the public finance management rationalization point of view
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 183-190